Physician-reported barriers to using evidence-based antibiotic prescription guidelines in primary care: protocol for a systematic review and synthesis of qualitative studies using the Theoretical Domains Framework. Issue 11 (1st November 2022) - Bursey, Krystal; Hall, Amanda; Pike, Andrea; Etchegary, Holly; Aubrey-Bassler, Kris; Patey, Andrea M; Romme, Kristen
Abstract : Introduction: Overprescription of antibiotics poses a significant threat to healthcare globally as it contributes to the issue of antibiotic resistance. While antibiotics should be predominately prescribed for bacterial infections, they are often inappropriately given for uncomplicated upper respiratory tract infections (URTIs) and related conditions, such as the common cold. This study will involve a qualitative systematic review of physician-reported barriers to using evidence-based antibiotic prescription guidelines in primary care settings and synthesise the findings using a theoretical basis. Methods and analysis: We will conduct a systematic review of qualitative studies that assess physicians' reported barriers to following evidence-based antibiotic prescription guidelines in primary care settings for URTIs. We plan to search the following databases with no date or language restrictions: MEDLINE, Web of Science, CINAHL, Embase, the Cochrane Library and PsycInfo. Qualitative studies that explore the barriers and enablers to following antibiotic prescription guidelines for URTIs for primary care physicians will be included. We will analyse our findings using the Theoretical Domains Framework (TDF), which is a theoretically designed resource based on numerous behaviour change theories grouped into 14 domains. Using the TDF approach, we will be able to identify the determinants of our behaviour of interest (ie, following antibiotic prescription guidelines for URTIs) and categorise them into the 14 TDF domains. This will provide the necessary information to develop future evidence-based interventions that will target the identified issues and apply the most effective behaviour change techniques to affect change. This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols guidelines. Ethics and dissemination: Ethical approval is not required. Findings will be published in a peer-reviewed journal and presented at conferences.